Possibilidades pedagógicas da Etnomatemática para a sala de aula - Rebouças, Ana Priscila Sampaio (2024)
This thesis deals with the pedagogical possibilities of Ethnomathematics for the classroom, within the school context. It arises from personal and professional experiences provided by involvement with this field of research, which prompted the pursuit of a Ph.D. in Teaching and led to the following question: what are the pedagogical possibilities of Ethnomathematics, as presented in brazilian academic production of theses and dissertations, that can support the teaching and learning of Mathematics in the classroom? In this direction, the general objective is to analyze the pedagogical possibilities of Ethnomathematics, as presented in brazilian academic production of theses and dissertations, which can support the teaching and learning of Mathematics in the classroom. The research, of a bibliographical nature and qualitative approach, has as its investigation corpus brazilian theses and dissertations related to the educational dimension of Ethnomathematics, indicated by leaders of specific research groups on Ethnomathematics and coordinators of the Red Internacional de Etnomatemática in Brazil. As an analysis method, it employs Content Analysis from the perspective of Bardin (1977) and Oliveira (2008). The results indicate that the pedagogical possibilities of Ethnomathematics in Brazil are related to the levels and modalities of brazilian education and include the recognition of students' insertion context for teaching and learning school content, based on the sociohistorical-cultural aspects of the school community, the identification of the desires of the students within a given class, the sensitization of the class towards conducting critical and creative pedagogical practices, the contextualized discussion of curriculum content, and the production of pedagogical material. The conclusions suggest that the pedagogical possibilities of Ethnomathematics can be realized in the most diverse classrooms across brazilian territory through pedagogical practices guided by Ethnomathematics that value the aspects of the school's insertion context and expand dialogues between the local and global, creating conditions for students to see themselves as contributors to a more just and dignified society for all people.